Performance of Existing Definitions and Tests for the Diagnosis of Invasive Fungal Diseases other than Invasive Candidiasis and Invasive Aspergillosis in Critically Ill, Adult Patients: A Systematic Review with Qualitative Evidence Synthesis - Daniele R. Giacobbe; Andrea Cortegiani; Ilias Karaiskos; Toine Mercier; Sofia Tejada; Maddalena Peghin; Cecilia Grecchi; Chiara Rebuffi; Erika Asperges; Valentina Zuccaro; Luigia Scudeller; Matteo Bassetti; et al. (Journal of Fungi, 2021)
The Fungal Infections Definitions in Intensive Care Unit (ICU) patients (FUNDICU) project aims to provide standard sets of definitions for invasive fungal diseases (IFDs) in critically ill, adult patients, including invasive aspergillosis (IA), invasive candidiasis (IC), Pneumocystis jirovecii pneumonia (PJP), and other non-IA, non-IC IFDs. The first step of the project was the conduction of separated systematic reviews of the characteristics and applicability to critically ill, adult patients outside classical populations at risk (hematology patients, solid organ transplant recipients) of available definitions and diagnostic tests for IFDs. We report here the results of two systematic reviews exploring the performance of available definitions and tests, for PJP and for other non-IA, non-IC IFDs. Starting from 2585 and 4584 records for PJP and other IFDs, respectively, 89 and 61 studies were deemed as eligible for full-text evaluation. However, only two studies for PJP and no studies for other IFDs met the FUNDICU protocol criteria for inclusion in qualitative synthesis. Currently, there is no sufficient solid data for directly evaluating the performance of existing definitions and laboratory tests for the diagnosis of PJP and other non-IA, non-IC IFDs in critically ill adult patients outside classical populations at risk.